Article Commentary: Further Research Needed to Support a Policy of Antiretroviral Therapy as An HIV Prevention Initiative. Issue 3 (April 2013) - Rodger, Alison J; Bruun, Tina; Vernazza, Pietro; Collins, Simon; Estrada, Vicente; Van Lunzen, Jan; Corbelli, Giulio M; Phillips, Andrew N; Lundgren, Jens D; ,
The results from the HPTN 052 trial have increased the focus on use of antiretroviral therapy (ART) for prevention of HIV transmission; however, condom use also effectively prevents HIV transmission. Studies in heterosexual serodiscordant couples with viral suppression have so far only reported follow-up data for 330 couple-years when condoms were not being used. Data are even more limited for anal sex in men who have sex with men. Additional data on the effectiveness of ART as prevention when practicing condom-less sex is urgently needed.